Study protocol for developing #CuttingCRC: a barbershop-based trial on masculinity barriers to care and colorectal cancer screening uptake among African-American men using an exploratory sequential mixed-methods design. Issue 7 (24th July 2019) - Rogers, Charles R; Okuyemi, Kola; Paskett, Electra D; Thorpe, Roland J; Rogers, Tiana N; Hung, Man; Zickmund, Susan; Riley, Colin; Fetters, Michael D
Abstract : Introduction: Colorectal cancer (CRC) is preventable, as screening leads to the identification and removal of precancerous polyps. African-American men consistently have the highest CRC mortality rates, and their CRC-screening uptake remains low for complex reasons. Culture-specific masculinity barriers to care may contribute to the low uptake among African-American men. Examining these barriers to care is vital as CRC screening may challenge cultural role expectations of African-American men, whose tendency is to delay help-seeking medical care. Barbershops provide a pathway for reaching African-American men with masculinity barriers to care who are not regularly receiving healthcare services and CRC screening. This study aims to develop and pilot test a theory-driven, culture-specific, barbershop-based intervention targeting masculinity barriers to care and CRC-screening uptake among African-American men ages 45–75. Methods and analysis: Guided by the theory of planned behaviour and the behaviour change wheel, we will use a multistage mixed-methods study design, beginning with an exploratory sequential approach to validate items for subsequent use in a pilot mixed-methods intervention. First, we will collect and analyse qualitative data from focus groups, cognitive interviews and expert item review to validate and test a culture-specific Masculinity Barriers to Care Scale (MBCS) among African-American men. Next, we will administer the MBCS to our target population as an online quantitative survey and evaluate the association between scores and CRC-screening uptake. Then, we will consider existing evidence-based approaches, our integrated results (qualitative +quantitative), and community input to design a culture-specific, behavioural intervention aimed at increasing CRC-screening uptake among African-American men and feasible for barbershop delivery. We will test the peer intervention in a pilot study with a two-arm cluster randomised design (six barbershops, randomised by site) to reduce contamination and account for barbershop culture differences. Our primary outcomes for the pilot are recruitment, sample size estimation, preliminary efficacy and acceptability. Ethics and dissemination: Ethics approval was obtained from the University of Utah Institutional Review Board (00113679), who will also be responsible for receiving communication updates regarding important protocol modifications. To ensure confidentiality, data dispersed to project team members will be blinded of any identifying participant information. Study results will be disseminated through publications in peer-reviewed journals, community dialogue sessions, and presentations at conferences. Trial registration number: ClinicalTrials.gov identifier: NCT03733197 (Pre-results);https://clinicaltrials.gov/ct2/show/NCT03733197